Development of Complement Factor H–Based Immunotherapeutic Molecules in Tobacco Plants Against Multidrug-Resistant Neisseria gonorrhoeae - Shaughnessy, Jutamas; Tran, Y; Zheng, Bo; DeOliveira, Rosane B.; Gulati, Sunita; Song, Wen-Chao; Maclean, James M.; Wycoff, Keith L.; Ram, Sanjay (Frontiers in Immunology, 2020)
Novel therapeutics against the global threat of multidrug-resistant Neisseria gonorrhoeae (Ng) are urgently needed. Gonococci possess several mechanisms to evade killing by human complement, including binding of factor H (FH), a key inhibitor of the alternative pathway. FH comprises 20 short consensus repeat (SCR) domains organized in a head-to-tail manner as a single chain. N. gonorrhoeae binds two regions in FH; domains 6 and 7 and domains 18 through 20. We designed a novel anti-infective immunotherapeutic molecule that fuses domains 18-20 of FH containing a D-to-G mutation in domain 19 at position 1119 (called FH*) with human IgG1 Fc. FH*/Fc retained binding to gonococci but did not lyse human erythrocytes. Expression of FH*/Fc in tobacco plants was undertaken as an alternative, economical production platform. FH*/Fc was expressed in high yields in tobacco plants (300-600 mg/kg biomass). The activities of plant- and CHO-cell produced FH*/Fc against gonococci were similar in vitro and in the mouse vaginal colonization model of gonorrhea. The addition of flexible linkers [e.g., (GGGGS)2 or (GGGGS)3] between FH* and Fc improved the bactericidal efficacy of FH*/Fc 2.7-fold. The linkers also improved PMN-mediated opsonophagocytosis about 11-fold. FH*/Fc with linker also effectively reduced the duration and burden of colonization of two gonococcal strains tested in mice. FH*/Fc lost efficacy: i) in C6 -/- mice (no terminal complement) and ii) when Fc was mutated to abrogate complement activation, suggesting that an intact complement was necessary for FH*/Fc function in vivo. In summary, plant-produced FH*/Fc represent promising prophylactic or adjunctive immunotherapeutics against multidrug-resistant gonococci.